2002
DOI: 10.3998/ark.5550190.0003.811
|View full text |Cite
|
Sign up to set email alerts
|

Generation and cycloaddition of semi-stabilized 2-azaallyllithiums via electrocyclic ring-opening or cycloreversion reactions

Abstract: Semi-stabilized 2-azaallyl anions, i.e., those bearing aryl groups, have been generated by either the electrocyclic ring-opening of N-lithioaziridines or the 1,3-anionic cycloreversion of N-lithioimidazolidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…As the spectroscopic and crystallographic data indicate, compound 6 unexpectedly adopts a dimeric structure . The proton NMR spectrum of 6 shows the characteristic signal for the CH 2 group of the saturated B/N heterocycle as a singlet at 4.44 ppm (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…As the spectroscopic and crystallographic data indicate, compound 6 unexpectedly adopts a dimeric structure . The proton NMR spectrum of 6 shows the characteristic signal for the CH 2 group of the saturated B/N heterocycle as a singlet at 4.44 ppm (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…In sharp contrast, due to the lower reactivity of imines, enantioselective 1,3-DCs of azomethine ylides with carbon–nitrogen double bonds are rare . The key reason for this situation is that the 1,3-DCs of azomethine ylides with imines might be reversible, , thus leading to low yields of the imidazolidines. Capturing imidazolidines in situ will be a good strategy to drive the reaction to completion for efficient construction of the chiral imidazolidine skeleton, which constitutes the core structure of many natural products, bioactive compounds, and important catalysts or ligands …”
mentioning
confidence: 99%
“…[33][34][35][36] However, limited progress has been made in this area ever since. [37][38][39][40][41][42] In 2002, Pearson and coworkers observed that the deprotonation of aldimines using LDA afforded self-1,3-dipolar cycloadducts in unsatisfactory yield and regioselectivity. 39 Thereafter, Cossío reported an unusual [3 + 2] autocyclization of an aldimine derived from an aromatic aldehyde and a glycine methyl ester in the presence of AgClO 4 , providing the corresponding imidazolidine in poor to moderate yields, albeit with high diastereoselectivity.…”
mentioning
confidence: 99%